Sulforaphane enhances irradiation effects in terms of perturbed cell cycle progression and increased DNA damage in pancreatic cancer cells - Naumann, Patrick; Liermann, Jakob; Fortunato, Franco; Weber, Klaus-Josef; Debus, Jürgen (PLOS ONE, 2017)
Sulforaphane (SFN), an herbal isothiocyanate enriched in cruciferous vegetables like broccoli and cauliflower, has gained popularity for its antitumor effects in cell lines such as pancreatic cancer. Antiproliferative as well as radiosensitizing properties were reported for head and neck cancer but little is known about its effects in pancreatic cancer cells in combination with irradiation (RT). In four established pancreatic cancer cell lines we investigated clonogenic survival, analyzed cell cycle distribution and compared DNA damage via flow cytometry and western blot after treatment with SFN and RT.
Gesehen am 26.09.2018